Socio-demographic determinants of tuberculosis patients attending directly observed treatment short course centre in urban Ghaziabad, Uttar Pradesh - Yadav, Manoj Kumar; Raghav, Mohit; Chaudhary, S. S.; ., Manisha (International Journal Of Community Medicine And Public Health, 2020)
Background: Tuberculosis was the first infectious disease declared by the WHO as a global health emergency. Men are more commonly affected than women. The case notifications were higher in males than in females most countries. The objective of the study was to assess socio-demographic determinants of tuberculosis patients attending directly observed treatment short course (DOTS) centre in Urban Ghaziabad. Methods: This was an observational cross-sectional study. The study was carried out in selected DOTS centres of district Ghaziabad. 850 study subjects age group more than 15 years were included. Multistage sampling was done. Numbers and percentage were used. SPSS version 13 was used for statistical analysis. Results: Majority 41.17% of tuberculosis (TB) patients belonged to 15-25 years age group. 30.58% patients were in 26-35 years age group followed by 23.52% in 36-45 years age group and least 4.70% were in >45 years age group. Majority 54.1% of TB patients were females that compared to 45.9% were males. Among tuberculosis patients majority 58.82% were married as compared to 40% were unmarried and least 1.18% were widow. 75.29% tuberculosis patients were Hindus as compared to 22.35 were Muslims and least 2.35% were Sikh/Christian. Among tuberculosis patients majority 44.71% were from nuclear family. 31.76% had joint family and least 23.53% had 3rd generation family. Conclusions: It was concluded that socio-demographic determinants were low. It was recommended to raise socioeconomic standard of population, give health education to improve personal habit and stop TB transmission.